Smallholder farmers access to climate information and climate smart adaptation practices in the Northern Region of Ghana - Alidu, Abdul-Fatah; Man, Norsida; Ramli, Nurul Nadia; Mohd Haris, Nur Bahiah; Alhassan, Amin (Elsevier, 2022)
In Ghana over 70% of people who are employed in the agricultural sector are smallholder farmers' living in less developed communities engaging in rudimentary agriculture. Climate change poses a serious threat to smallholder farmers which impacts on their income, food security and wellbeing. Climate information could be a vital resort for smallholder farmers' adoption of climate smart adaptation strategies in order to better manage climate risk. This study is aimed at investigating factors that influence smallholder farmers' joint decision to access climate information as well as adopt climate smart adaptation practices in the Northern Region. Data used was collected from a cross-sectional survey of 475 smallholder farmers'. The joint decision of smallholder farmers to access climate information and also adopt climate smart adaptation practices was analysed by using bivariate probit regression model. The econometric estimates reveal that age, household size, farm income, access to agricultural extension services and assets are the key drivers of smallholder farmers joint decision to access climate information and adopt climate smart adaption practices. Government, district assemblies and non governmental organisations supporting smallholder farmers’ adoption of climate smart adaptation strategies in order to overcome climate risk should also assist in the accessibility of climate information since they complement one another. Smallholder farmers literacy and knowledge level should be increased through non-formal and informal educational programmes, and extension education using the farmer-field schools method.